Fuzzy Petri nets and industrial applications: a review - Zhou, Kai Qing (Springer Netherlands, 2016)
Fuzzy Petri net (FPN) provides an extremely competent basis for the implementation of computing reasoning processes and the modeling of systems with uncertainty. This paper reviews recent developments of the FPN and its industrial applications. Several important aspects of FPN’s background, history and formalisms are discussed, including the reasoning algorithm and relevant industrial applications; after which we present our conclusions and suggestions for future research